The Extraction of Platinum and Palladium from Supported over Al2O3 Spent Catalysts Using Alternating Current - K. Dosumov (Eurasian Chemico-Technological Journal, 2000)
The results of investigation of extraction of platinum and palladium from spent catalysts of gases of gasoline and diesel engines and oil refining purification into solution of HCl at anodic polarization of graphite electrodes by alternating current are demonstrated. Influence of temperature, current density, concentration of HCl and other factors have been studied. The optimal parameters of electrolysis with extraction into solution of 98-100% noble metals have been determined. feedstocks to desirable higher added-value products.